The World Bank Group, country assistance strategy for the Democratic Socialist Republic of Sri Lanka, 2003-2006. - The World Bank; World Bank Group (Colombo : World Bank Group, 2003)
On the economic conditions and policies of Sri Lanka in the context of economic assistance from the World Bank.
Includes bibliographical references.
Keywords: Economic assistance -- Sri Lanka; Sri Lanka -- Economic conditions; Sri Lanka -- Economic policy